Advancing horizons in vegetable cultivation: a journey from ageold practices to high-tech greenhouse cultivation—a review - Ahmed, Nazir; Zhang, Baige; Deng, Lansheng; Bozdar, Bilquees; Li, Juan; Chachar, Sadaruddin; Chachar, Zaid; Jahan, Itrat; Talpur, Afifa; Gishkori, Muhammad Saleem; Hayat, Faisal; Tu, Panfeng (Frontiers in Plant Science, 2024)
Vegetable cultivation stands as a pivotal element in the agricultural transformation, illustrating a complex interplay between technological advancements, evolving environmental perspectives, and the growing global demand for food. This comprehensive review delves into the broad spectrum of developments in modern vegetable cultivation practices. Rooted in historical traditions, our exploration commences with conventional cultivation methods and traces the progression towards contemporary practices, emphasizing the critical shifts that have refined techniques and outcomes. A significant focus is placed on the evolution of seed selection and quality assessment methods, underlining the growing importance of seed treatments in enhancing both germination and plant growth. Transitioning from seeds to the soil, we investigate the transformative journey from traditional soil-based cultivation to the adoption of soilless cultures and the utilization of sustainable substrates like biochar and coir. The review also examines modern environmental controls, highlighting the use of advanced greenhouse technologies and artificial intelligence in optimizing plant growth conditions. We underscore the increasing sophistication in water management strategies, from advanced irrigation systems to intelligent moisture sensing. Additionally, this paper discusses the intricate aspects of precision fertilization, integrated pest management, and the expanding influence of plant growth regulators in vegetable cultivation. A special segment is dedicated to technological innovations such as the integration of drones, robots, and state-of-the-art digital monitoring systems in the cultivation process. While acknowledging these advancements, the review also realistically addresses the challenges and economic considerations involved in adopting cutting-edge technologies. In summary, this review not only provides a comprehensive guide to the current state of vegetable cultivation but also serves as a forwardlooking reference, emphasizing the critical role of continuous research and the anticipation of future developments in this field.